Elderly people in Costa Rica: An approach to the perceptions about their Life Quality - Alfaro Vargas, Noelia (2021)
The objective of the study was to determine the perceptions of people aged 60 years and over residing in the country on psychosocial components of social support, personal well-being and spirituality. This study was developed using a quantitative approach, via telephone survey as the main technique for collecting information. Among the study’s main results, it was discovered that the higher the educational level of the participants, the better they rated their quality of life. Regarding the correlation between suffering or not suffering from a disease or medical condition, and the level of satisfaction with health, it was found that people who indicated that they did not suffer from any disease seemed to be more satisfied with their health. Regarding satisfaction with life, 94.3% of the interviewees indicated that they were satisfied with life.Finally, regarding spirituality, 96.2% indicated that their spiritual strength helped them to feel happy.